The absence of the embryo in the pseudopregnant uterus alters the deposition of some ECM molecules during decidualization in mice. (June 2015) - Covarrubias, Ambart E. C.; Barrence, Fernanda C.; Zorn, Telma M. T.
Abstract The embryo-implantation promotes deep changes in the uterus resulting in the formation of a new structure at the maternal–fetal interface, the decidua. Decidualization can also be induced in pseudopregnant rodents resulting in a structure called deciduoma that is morphologically and functionally similar to the decidua. Previous studies from our and other laboratories demonstrate that in rodents, decidualization of the endometrium requires remarkable remodeling of the endometrial extracellular matrix (ECM) that is mainly coordinated by estradiol and progesterone. The influence of the embryo in this process, however, has not yet been investigated. To enlarge the knowledge on this subject, the present study investigates the behavior of a set of ECM molecules, in the absence of paracrine cues originated from the embryo. For that deciduoma was induced in pseudopregnant Swiss mice, and the distribution of collagen types I, III, IV, V and the proteoglycans decorin and biglycan was investigated by immunolabeling from the fifth to the eighth day of pseudopregnancy. It was observed the deposition of collagen types III and IV as well as decorin and biglycan was similar to that previously described by our group in the decidua. However, in the absence of the embryo, some differences occur in the distribution of collagen types I and V, suggesting that beside the major role of ovarian hormones on the endometrial ECM remodeling, molecular signals originated from the conceptus may influence this process.